Sequential learning of psychomotor and visuospatial skills for laparoscopic suturing and knot tying: a randomized controlled trial “The Shoebox Study” DRKS00008668 - Nickel, Felix; Hendrie, Jonathan D.; Kowalewski, Karl-Friedrich; Bruckner, Thomas; Garrow, Carly R.; Mantel, Maisha; Kenngott, Hannes Götz; Romero, Philipp; Fischer, Lars; Müller, Beat P. (Langenbeck's archives of surgery, 2016)
Learning curves for minimally invasive surgery are prolonged since psychomotor skills and visuospatial orientation differ from open surgery and must be learned. This study explored potential advantages of sequential learning of psychomotor and visuospatial skills for laparoscopic suturing and knot tying compared to simultaneous learning.
Gesehen am 09.10.2020